Critical Analysis of the Role of Teachers and Parents in an Effort to Improve the Disciplinary Character of Students at SD UMP Banyumas - Megawati Megawati; Ine Kusuma Aryani (Green Publisher, 2024)
This study aims to: 1) describe the role of teachers in enhancing the disciplinary character of students at SD UMP Banyumas, 2) explore the role of parents in this process, 3) identify supporting and inhibiting factors, 4) evaluate the effectiveness of teachers' roles, and 5) analyze the overall impact of these roles on students' discipline. The research involves principals, teachers, parents, and students using a qualitative approach with a case study method. Data were gathered through observations, interviews, and documentation and analyzed using data reduction, data presentation, and conclusion drawing, supported by source and technique triangulation. The findings reveal that: 1) Teachers act as educators, guides, role models, motivators, and evaluators. 2) Parents contribute to children's discipline by providing explanations and advice, modeling behavior, demonstrating compassion, supervising, and teaching religious values. 3) Supporting factors include a conducive environment, adequate facilities, and strong support from teachers, parents, and the community, whereas inhibiting factors encompass negative peer influence, children's preference for play, media distractions, and the absence of parental supervision. 4) Evaluation methods involve observation, self-assessment, and peer assessment, with results communicated to parents. 5) While teachers generally perform their roles effectively, some areas need improvement. Effective strategies used by teachers include habituation, modeling, lectures, and simulations. Parental involvement is crucial in fostering self-discipline from an early age.